EVALUASI REGULASI PERMAINAN INTERAKTIF ELEKTRONIK DI INDONESIA (STUDI TERHADAP TRANSAKSI ELEKTRONIK ATAS BENDA VIRTUAL) - Anwar Saleh Hasibuan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: Transactions through internet media, especially transactions for goods, are interesting things to do a study, especially if the goods being transacted are intangible goods or also known as virtual objects. The problem in this study is related to the legality of electronic transactions on virtual objects in the regulation of electronic interactive games in Indonesia and the legality of electronic transactions on ideal virtual objects in the regulation of electronic interactive games in Indonesia. This type of research is normative legal research. Judging from its nature, the nature of this research is descriptive analytical which is a study to describe and analyze existing problems and is included in the type of library research. Electronic transactions for virtual objects in the regulation of electronic interactive games in Indonesia, such as Mobile Legends: Bang Bang, Player Unknown's Battlegrounds (PUBG), and Call of Duty, are declared valid if the subjective and objective conditions of the electronic contract are met, namely there is an agreement between the parties. The legality of electronic transactions for virtual objects that are ideal in the regulation of electronic interactive games in Indonesia is that online games that are legal and not illegal to be played and prohibition of any illegal transaction patterns in legal online games, such as gambling simulations (roulette) in the game or other gambling simulations that have an economic advantage for online game owners. Keywords: Electronic Transactions, Virtual Objects, Electronic Interactive Games